Education Communication in the English Learning Process - Jetas Rahman; Afrizal; Ernita Arif (International Journal of Science and Society, 2019)
This research was conducted with the aim of analyzing instructional communication between teachers and students in learning English and the obstacles faced by teachers and students in achieving learning communication objectives located at SMPN 25 Solok Selatan. This research uses qualitative research. Determination of informants by means of purposive sampling, research data obtained through in-depth interviews, observation, and documentation. Data processing techniques using the model of Miles and Huberman analysis and data validity with triangulation. The results showed that in the learning or instructional communication process: (1) communicators were still dominated by teachers while many students were still passive; (2) messages are arranged and designed by teachers based on the applicable curriculum taking into account the different backgrounds of students; (3) the method used is the lecture, demonstration, discussion, and question and answer method; and (4) feedback in the communication process is done directly by students both verbally and nonverbally. Barriers that occur in the learning communication process include the use of language by communicators that are less understood by students, the limited media used and the lack of motivation of students in learning English.